Facile preparation of sulphur-doped graphene quantum dots for ultra-high performance ultraviolet photodetectors. (23rd August 2017) - Gao, Shuxiong; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Lai, Sin Ki; Yuan, Shouzhang; Lau, Shu Ping
Abstract : Sulphur-doped GQDs were prepared using a novel co-combustion method (T-X-J method), and ultra-high performance UV photodetectors based on S-GQDs were fabricated. Abstract : Sulphur-doped graphene quantum dots (S-GQDs) were prepared in this work by a novel and facile method using the co-combustion (T-X-J method) of a liquid mixture of paraffin oil and carbon disulphide (CS2 ). Ultra-high performance ( R : 307 A W −1 ; D *: 1.5 × 10 14 Jones) ultraviolet photodetectors based on S-GQDs were fabricated under ambient conditions, shedding light on the fabrication of graphene based high-performance optoelectronic devices.